Tissue-Specific Diversity of Group 2 Innate Lymphoid Cells in the Skin - Kobayashi, Tetsuro; Moro, Kazuyo (Frontiers in Immunology, 2022)
Since the discovery of group 2 innate lymphoid cells (ILC2s), their developmental pathways, mechanisms of activation and regulation, and immunological roles in the steady state and in disease have been reported in various organs. ILC2s, which produce large amounts of IL-5 and IL-13 in response to tissue-derived factors and are essential in inducing and promoting allergic inflammation, have also been found to play multifaceted roles in maintaining tissue homeostasis. While T cells respond to foreign antigens, the activation of ILC2s is regulated by various tissue-derived factors, including cytokines, lipids, hormones, and neurotransmitters, and ILC2s show different phenotypes depending on the tissue in which they are present. In this review, we discuss tissue-specific characteristics of ILC2s in the skin. ILC2s, as defined in the lungs, intestinal tract, and adipose tissue, cannot be directly applied to cutaneous ILC biology, because skin ILC2s exhibit different aspects in the expression patterns of cell surface markers, the response to tissue-derived cytokines and the functions in both steady-state and inflammation. The skin contains ILCs with features of both ILC2s and ILC3s, and the plasticity between ILCs complicates their characters. Furthermore, the epidermis, dermis, and subcutaneous tissues contain ILCs with different characteristics; their localization has expanded our understanding of ILC function. Single-cell RNA-seq technology has further elucidated the role of ILCs in human skin and disease pathogenesis. Overall, this review discusses the phenotypical and functional heterogeneity of skin ILCs reported in recent years and highlights future directions within the field of ILC biology.